A review of environmental aspect of rare earth element extraction processes and solution purification techniques. (30th March 2022) - Talan, Deniz; Huang, Qingqing
Highlights: Various aspects of rare earth elements were compiled from a global perspective. New research initiatives and resource exploration on rare earths were investigated. The environmental impact of rare earth element extraction was reviewed. Regulatory approaches for radioactivity issues and waste disposal were addressed. Separation processes for thorium, uranium and rare earth elements were reviewed. Abstract: Rare earth elements (REEs) are vital for the technology, military, and defense industries. They have been recognized as critical due to potential scarcity, supply constraints, and lack of minable concentrations. Therefore, alternative sources are needed to meet the demand and continue manufacturing rare earth-dependent products. However, the environmental prospect of rare earth mining was not investigated enough, and comprehensive studies are lacking. It demands serious consideration as toxic radionuclides are seen in the same mineralization as rare earths regardless of their primary or secondary sources. The concentration of these hazardous trace elements may be elevated as a result of extraction and beneficiation processes. Unless proper separation and disposal are performed, these radionuclides accumulate on the surface of the soil or integrate with aquatic systems, which consequently raise environmental and health concerns. This review manuscript compiled the environmental impact and aspect of rare earth extraction processes while addressing separation techniques for these radioactive materials from rare earths, emphasizing selective precipitation, solvent extraction, and solid-phase separation.